Effect of Beta Thalassemia Trait in Pregnancy (Community Based Medical Journal, 2024)
A cross-sectional, observational study was conducted to determine the effects of beta thalassemia trait in pregnancy. A total of 150 pregnant women diagnosed with beta thalassemia trait in Bangladesh Navy Ship (BNS) Patenga Hospital, at Chattogram, Bangladesh, having regular antenatal care and delivery, between January and December of 2022, were included in the study. Thalassemia status was diagnosed by Hb-electrophoresis. Most of the patients belonged to the age group 19-35 years. 30.46% of women had normal hematocrit level. During pregnancy women suffered from severe anemia (14%) and mild anemia (55.33%) (P0.05). Most of the women (76.66%) delivered babies at her 36-39 weeks of gestational age,18.67% delivered at or after 40 weeks of gestation and 4.67% delivered baby before 36 weeks (P